Analysis of Hydrogeochemical Vulnerability - Moraru, Constantin (Springer Hydrogeology,, 2018)
This monograph instructs the reader on how to analyze the hydrogeochemical vulnerability. It introduces notions of geochemical signals, points of migration of pollutants in the unsaturated zone, and new hydrogeochemical classifications. Three test sites in the USA, Germany, and Moldova are described as case studies accompanied by illustrative data. The authors presuppose for future readers only the background mathematics and elementary knowledge of hydrogeology. The presented methodology is both for local and regional assessments. It is simple, does not need implication of high qualification specialists and can be applied to test the groundwater quality. The book is useful for undergraduate, graduate, master, and PhD students as well as water quality specialists, ecologists and geology professionals.